Identifying climate refugia and bright spots for highly mobile species - Nerea Lezama-Ochoa; Heather Welch; Jennifer A. Brown; Scott R. Benson; Karin A. Forney; Briana Abrahms; Mercedes Pozo Buil; Michael G. Jacox; Barbara A. Muhling; Owen R. Liu; Thomas A. Clay; Ryan Freedman; et al. (npj Ocean Sustainability)
Abstract Climate-driven shifts in species distributions can undermine the effectiveness of protected areas. We present a framework to facilitate climate change adaptation planning by identifying where highly migratory species habitats will persist (climate refugia), emerge (bright spots), disappear (dark spots), or remain unsuitable based on model analysis by 2100. When applied to eight species in the California Current System, we found that, on average, 37% of habitats are expected to be climate refugia, 9% are bright spots, and 13% are dark spots within National Marine Sanctuaries by 2100. Species responses differ: leatherback turtles may find refuge near U.S. coastal waters (18%), blue whales may show increased bright spots (41%), and humpback whales may exhibit more dark spots (44%). These findings highlight the need to integrate species projections into spatial planning to enhance species conservation. Our approach can be applied globally to evaluate the effectiveness of protected areas in safeguarding biodiversity under climate change.